Issues in Clinical Learning Environment Faced by Female Nursing Students at Jamshoro, Pakistan: Clinical Learning Environment Faced by Female Nursing Students - Chandio, Irfan Ali; Channar, Husan Bano; Khatoon, Janul; Abass, Zaheer; Areej, Sana; Aghani, Shaista (Pakistan Journal of Health Sciences, 2024)
Hospital-based education provides a supportive environment for nursing students who accept challenges for their profession. Although nursing is primarily a skill-based profession, clinical training is an important component of the growing nursing field. This empowers nursing students to integrate theoretical information into their psychomotor abilities, which they may then use in patient care. Objective: To identify issues in the clinical learning environment faced by female nursing students at Jamshoro. Methods: A descriptive cross-sectional study was directed at the public sector Liaquat College of Nursing attached to Liaquat University Hospital in Jamshoro from November 2023 to April 2024. A convenience sampling technique was utilized, and the research tool was adopted with some modifications and expert consultations to collect the data. Nursing students enrolled in clinical practice for six months and performed data analysis using IBM SPSS version 25.0. Results: The mean age of the participants in this study was evaluated at 21.5 years, with a standard deviation of 0.664 years. According to our findings, 24.6% of participants assigned their duties to the pediatric ward. 82.4% of participants were overseen by a single teacher, 78.3% lacked personal protection equipment, and 72.5% reported a lack of cooperation between the College of Nursing and the hospital. Conclusions: It was concluded that most participants are dissatisfied with clinical education, thus, reducing the shortage of clinical faculty, providing personal protective equipment, and developing good coordination between nursing colleges and hospitals can reduce issues faced by nursing students in clinical settings, thereby improving patient care.